Socialism and the Way of Thought - Kis, Sandor (Problemos, 1982)
The socialist way of thought as a factor of human consciousness, based on the theory of scientific communism and defining man’s approach to the problems of the present-day epoch, is considered. The principal specific features of the above way of thought are being defined. These are: priority of political needs of the working class for an ideological preparation in any form of social activity as well as predominance of collectivism in this process.